Perspectives of Older Adults on Aging Well: A Focus Group Study - Hadeel Halaweh; Synneve Dahlin-Ivanoff; Ulla Svantesson; Carin Willén (Journal of Aging Research)
Background. With increasing number of older adults worldwide, promoting health and well-being becomes a priority for aging well. Well-being and physical and mental health are closely related, and this relation may become more vital at older ages as it may contribute to aging well. The state of well-being is a multifaceted phenomenon that refers to an individual’s subjective feelings, and exploring perspectives of older adults on aging well is developing to be an important area of research. Therefore, the aim of this study was to explore perceptions on aging well among older adult Palestinians ≥60 years. Methods. A qualitative research design in the context of focus group discussions was used; seven focus groups were conducted including fifty-six participants (aged 63–81 years). Data were analyzed using a qualitative interpretative thematic approach described by Braun and Clarke. Results. Three major themes were identified, “sense of well-being,” “having good physical health,” and “preserving good mental health.” The participants perceived that aging well is influenced by positive feelings such as being joyous, staying independent, having a life purpose, self-possessed contentment, and financially secured, in addition to be socially engaged and enjoying good physical and mental health. Conclusion. This study contributes to get a better insight concerning older adults’ perspectives on aging well. Enhancing physically active lifestyle, participation in social and leisure activities, healthy eating habits, having a purpose in life, and being intellectually engaged are all contributing factors to aging well. Vital factors are to be considered in developing strategic health and rehabilitative plans for promoting aging well among older adults.